ANALISIS PEMBELAJARAN PANCASILA BERBASIS HUMANIS DALAM MENUMBUHKAN KESADARAN KEBANGSAAN PESERTA DIDIK: STUDI LITERATUR - Asti Wanda Rinjani; Heryanti Heryanti (Penerbit Widina, Widina Media Utama, 2026)
This study was motivated by the fact that Pancasila education remains focused on cognitive aspects, making it less effective at instilling national values deeply in students. This situation has led to a decline in tolerance, social solidarity, and patriotism among the younger generation. This study aims to analyze the contribution of humanistic-based Pancasila education in fostering students’ national consciousness through a literature review approach. The method used is a literature review with data collection techniques involving the search for scientific articles from Google Scholar, Sinta, and indexed international journals from 2015 to 2025. Article selection was conducted systematically through the stages of identification, screening, and eligibility until 15 relevant articles were obtained for analysis. The research results indicate that humanistic-based learning is capable of enhancing national consciousness through the more meaningful internalization of Pancasila values, the strengthening of empathy and tolerance, and increased active student participation in the learning process. Thus, the humanistic approach is effective in shaping a national character that is contextual, reflective, and sustainable. ABSTRAKPenelitian ini dilatarbelakangi oleh pembelajaran Pancasila yang masih berorientasi pada aspek kognitif sehingga kurang mampu menginternalisasikan nilai-nilai kebangsaan secara mendalam kepada peserta didik. Kondisi tersebut berdampak pada melemahnya sikap toleransi, solidaritas sosial, dan rasa cinta tanah air di kalangan generasi muda. Penelitian ini bertujuan untuk menganalisis kontribusi pembelajaran Pancasila berbasis humanis dalam menumbuhkan kesadaran kebangsaan peserta didik melalui pendekatan studi literatur. Metode yang digunakan adalah studi literatur dengan teknik pengumpulan data melalui penelusuran artikel ilmiah dari Google Scholar, Sinta, dan jurnal internasional terindeks pada rentang tahun 2015–2025. Seleksi artikel dilakukan secara sistematis melalui tahap identifikasi, screening, dan kelayakan hingga diperoleh 15 artikel yang relevan untuk dianalisis. Hasil penelitian menunjukkan bahwa pembelajaran berbasis humanis mampu meningkatkan kesadaran kebangsaan melalui internalisasi nilai-nilai Pancasila yang lebih bermakna, penguatan sikap empati dan toleransi, serta peningkatan partisipasi aktif peserta didik dalam proses pembelajaran. Dengan demikian, pendekatan humanis efektif dalam membentuk karakter kebangsaan yang kontekstual, reflektif, dan berkelanjutan